Pengaruh Media Film Pendek pada Channel Youtube Paniradya Kaistimewan terhadap Kemampuan Menulis Cerpen Siswa Kelas XI SMA Negeri 2 Malingping Tahun Pelajaran 2023/2024 - Ninawati, Ninawati (Jurnal Artikula, 2024)
The influence of short film media on the Paniradiya Kaistimewan YouTube channel on the short story writing skills of class XI students of SMA Negeri 2 Maingping. This study aims to determine the influence of short film media on class XI students of SMA Negeri 2 Malingping. This study was conducted based on the problem of low short story writing skills in high school students which is characterized by students having difficulty writing short stories. This study aims to determine the difference in the influence of writing skills of students who learn using short film media with students who use digital image media. The method in this study uses the Quantitative method. The population and sample in this study were class XI students of SMA Negeri 2 Malingping as many as 2 classes selected randomly or Random Sampling. The instrument used in this study was a short story writing ability test. The test used was a question-type test. Based on the results of the data analysis, the results of this study concluded: There is a difference in the influence of the ability to write news texts of students who learn using short film media with students who learn using digital image media. The ability to write short stories of students who receive short film learning is better than students who learn using digital image media. This can be seen from the results of the hypothesis test, namely by using the Independent Samples Test which was obtained from a sig value of 0.021 <0.05, meaning that the variance between groups is not the same. So it can be concluded that there is a significant difference in the increase in the Influence of Short Film Media on the Ability to Write Short Stories of High School Students